2017
DOI: 10.29115/sp-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Explanation: A Strategy to Minimize Nonresponse in Demographic Items Among Low-Income Racial and Ethnic Minorities

Abstract: There is a high rate of nonresponse for demographic items in survey research, particularly for racial and ethnic minority respondents. This present study examined whether providing an explanation to racial and ethnic minority respondents prior to asking a set of demographic questions would increase respondents’ motivation to reduce nonresponse to gender, income, age, and race items. Using a cross-sectional, randomized comparison design, 99 respondents were randomly assigned to two groups. Group 1 did not recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…When detailed frame data are not available to describe respondents, self-report is needed to understand respondent characteristics. However, some demographic questions are largely recognized as sensitive (Tourangeau and Yan 2007) and may be left unanswered due to confidentiality concerns or the perception that the question is threatening or difficult to answer (Lor et al 2017). Furthermore, respondents may choose to skip the entire survey due to confidentiality concerns (Singer, Hippler, and Schwarz 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When detailed frame data are not available to describe respondents, self-report is needed to understand respondent characteristics. However, some demographic questions are largely recognized as sensitive (Tourangeau and Yan 2007) and may be left unanswered due to confidentiality concerns or the perception that the question is threatening or difficult to answer (Lor et al 2017). Furthermore, respondents may choose to skip the entire survey due to confidentiality concerns (Singer, Hippler, and Schwarz 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have attempted to attenuate the sensitive nature of demographic questions using a variety of methods, for example, by stating the purpose of collecting demographic items, placing demographic questions at the end of the survey (Lor et al 2017), or assuring respondent confidentiality (Singer, Hippler, and Schwarz 1992). However, the impact of whether and how demographic questions are asked on response rates and other data quality measures is largely unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that individuals with low education levels would remain silent because of insufficient capability to understand (19), which is common in the current study. Therefore, more information is needed to support them in the survey (20).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to response or not is affected by other unobserved characteristics. People who are in a lower social position, with a lower educational attainment, female, African American, or older in age have higher item nonresponse rate (Lor, Bowers, Krupp, & Jacobson, 2017;Ross & Reynolds, 1996). Beatty and Herrmann (2002) suggest that other cognitive and motivational factors also contribute to the income nonresponse, such as cognitive ability to remember and retrieve relevant information to report, judgment of the level of precision required by the survey and one's willingness to answer.…”
Section: Robustness Checksmentioning
confidence: 99%